Effects of Poloxamer 188 on red blood cell membrane properties in sickle cell anaemia. (5th February 2016) - Sandor, Barbara; Marin, Mickaël; Lapoumeroulie, Claudine; Rabaï, Miklos; Lefevre, Sophie D.; Lemonne, Nathalie; El Nemer, Wassim; Mozar, Anaïs; Français, Olivier; Le Pioufle, Bruno; Connes, Philippe; Le Van Kim, Caroline
Summary: Vaso‐occlusive crisis (VOC) is the main acute complication in sickle cell anaemia (SS) and several clinical trials are investigating different drugs to improve the clinical severity of SS patients. A phase III study is currently exploring the profit of Velopoloxamer in SS during VOCs. We analysed, in‐vitro, the effect of poloxamer (P188) on red blood cell (RBC) properties by investigating haemorheology, mechanical and adhesion functions using ektacytometry, microfluidics and dynamic adhesion approaches, respectively. We show that poloxamer significantly reduces blood viscosity, RBC aggregation and adhesion to endothelial cells, supporting the beneficial use of this molecule in SS therapy.